Analisis Gaya Kepemimpinan Demokratis Di Hotel XY Jakarta - Putri Arnindya; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Journal Economic Excellence Ibnu Sina, 2024)
The hotel's goal in running its business is of course to provide the best service to guests who stay overnight at the hotel or guests who only use the facilities or services available at the hotel. If a hotel can provide good service then the hotel has achieved success in accordance with its objectives. Success in achieving a goal is something that can be measured as the success of a company or agency. a leader is needed who is able to bring the hotel to its goals. Democratic leadership is a leadership style in which the leader involves team or group members in the decision-making process. This leadership style creates an environment where team members feel they have a voice and their contributions are valued. Democratic leaders support participation, cooperation, and shared leadership to achieve common goals. This research uses a qualitative approach. Secondary data is obtained externally through references from articles, journals and books. The sampling technique uses a non-probability sampling method with a purposive sampling method. The purpose of this research is to find out how the leadership of the food and beverage department of XY Jakarta Hotel involves employees in decision making to obtain wise decision results.